Global Commodity Markets : Review and Price Forecast - World Bank (Washington, DC, 2017)
This is a companion to the Global Economic Prospects 2010. Most commodity prices reached historical highs in mid-2008, giving rise to the longest and broadest commodity boom of the post-WWII period. Apart from strong and sustained economic growth, the boom was fueled by numerous factors including years of low prices and low investment; a weak dollar; and investment fund activity. Rapid economic growth caused global stocks of many commodities to fall to levels not seen since the early 1970s, in turn accelerating the price increases that peaked in 2008. Further exacerbating the demand and supply mismatch were the diversion of some food commodities to the production of biofuels, adverse weather conditions, and government policies such as export bans and prohibitive taxes. The financial crisis that erupted in September 2008 and the subsequent global economic downturn relieved most of the demand-side pressures and induced sharp price declines across most commodity sectors. The largest declines occurred in industrial commodities such as metals (which had also registered the greatest gains in the early 2000s). Between July 2008 and February 2009, prices of energy declined by two-thirds while those of metals dropped by more than half. Prices of agricultural goods retreated by more than 30 percent, with prices of edible oils dropping by 42 percent. The troughs in energy and non-energy indices broadly coincided with troughs in global economic activity (particularly in China and East Asia).